On-fiber Derivatization for Determination of Ethylene Glycol Concentration in Lubricant oil By SPME-GC/MS - Lee, Joon-Bae; Shon, Shungkun; Kwon, O-Seong; Min, Ji Sook; Kim, Nam Yee; Paeng, Ki-Jung (Bulletin of the Korean Chemical Society, 2016)
Reaction scheme of ethylene glycol (EG) and the internal standard (IS) with cyclohexanone (CH‐one).